"We Are Our Only Way Forward": Dialogic Re-imaginings and the Cultivation of Homeplace for Girls, Women, and Femmes of Color. (December 2022) - Player, Grace D.; Ybarra, Mónica González; Brochin, Carol; Brown, Ruth Nicole; Butler, Tamara T.; Cervantes-Soon, Claudia; Gill, Victoria S.; Kinloch, Valerie; Price-Dennis, Detra; Saavedra, Cinthya M.; Sealey-Ruiz, Yolanda
This article narrates the contours of a digital "kitchen table talk"–a conversation that brought together WoC from various areas of literacy and language education to discuss the state of the field and the next steps in transforming literacy studies and education for GFoC. Using bell hooks's concept of "homeplace, " we bring together the reflections of eleven WoC across intersected Black, Latina, and Asian identities to examine the realities of GFoC, the urgency around their lives and needs, as well as self-examination of our role in the academy taking up feminist projects with GFoC.